Protein-Induced Modulation of Chloroplast Membrane Morphology - Machettira, Anu B.; Groß, Lucia E.; Tillmann, Bodo; Weis, Benjamin L.; Englich, Giesela; Sommer, Maik S.; Königer, Martina; Schleiff, Enrico (Frontiers in Plant Science, 2012)
Organelles are surrounded by membranes with a distinct lipid and protein composition. While it is established that lipids affect protein functioning and vice versa, it has been only recently suggested that elevated membrane protein concentrations may affect shape and organization of membranes. We analysed the effects of high chloroplast envelope protein concentrations on membrane structures using an in vivo approach. Transient expression of outer envelope proteins or protein domains such as TM-CHUP1-GFP, OEP7-GFP or OEP24-GFP at high levels led to the formation of punctate, circular and tubular membrane protrusions. Expression of inner membrane proteins such as Tic20II-GFP led to membrane protrusions including invaginations. Using increasing amounts of DNA for transfection, we show that the frequency, size and intensity of these protrusions increased with protein concentration. The membrane deformations were absent after cycloheximide treatment. Co-expression of TM-CHUP1-Cherry and Tic20II-GFP led to membrane protrusions of various shapes and sizes including some stromule-like structures, for which several functions have been proposed. Interestingly, some structures seemed to contain both proteins, while others seem to contain one protein exclusively, indicating that outer and inner envelope dynamics might be regulated independently. While it was more difficult to investigate the effects of high levels of membrane proteins on mitochondrial membrane shapes using confocal imaging, it was striking that the expression of the outer membrane protein Tom20 led to more elongated mitochondria. We discuss that the effect of protein concentrations on membrane structure is possibly caused by an imbalance in the lipid to protein ratio and may be involved in a signaling pathway regulating membrane biogenesis. The observed phenomenon provides a valuable experimental approach to investigate the relationship between lipid synthesis and membrane protein expression in future studies.